2019
DOI: 10.1002/htj.21584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SWCNTs and MWCNTs Maxwell MHD nanofluid flow between two stretchable rotating disks under convective boundary conditions

Abstract: The aim of the current analysis is to investigate heat and mass transfer characteristics of single and multi-walled water-based carbon nanotubes Maxwell nanofluid flow between continuously rotating stretchable disks under the sway of chemical reaction and radiation. Boundary conditions of the convective type of temperature are employed at both lower and upper rotating disks in the preparation. Similarity variables are employed to transform the governing partial differential equations into the nonlinear ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Nadeem et al [13] conducted a numerical study to reveal that water-based SWCNT-MWCNT hybrid nanoliquid has a better heat transfer rate when balanced against SWCNT-water nanoliquid. Sreedevi and Reddy [14] performed a comparative study on the effect of water-based SWCNTs and MWCNTs Maxwell nanoliquid flow between two stretchable rotating disks. Some important analyses concerning CNTs are given in [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Nadeem et al [13] conducted a numerical study to reveal that water-based SWCNT-MWCNT hybrid nanoliquid has a better heat transfer rate when balanced against SWCNT-water nanoliquid. Sreedevi and Reddy [14] performed a comparative study on the effect of water-based SWCNTs and MWCNTs Maxwell nanoliquid flow between two stretchable rotating disks. Some important analyses concerning CNTs are given in [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Aman et al 10 have analyzed the heat transfer effect on unsteady free convection flow of Maxwell nanofluids past a vertically static plate. Heat and mass characteristics of MWCNTs and SWCNTs Maxwell nanofluids between continuously rotating disks in the presence of radiation are studied by Sreedevi and Reddy 11 . Irfan et al 12–15 have analyzed the impact of heat sink/source, radiation, and chemical reaction on MHD Maxwell nanofluid past a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The mass and heat transfer quality of SWCNT/MWCNT water-based MHD Maxwell nanoliquid flow between rotating stretchable disks has been investigated by Sreedevi and Sudarsana Reddy. 10 Eid et al 11 conducted a numerical study on the MHD blood-based SWCNT nanofluid flow through a circular cylinder considering linear heat source/sink, nonlinear thermal radiation, and nanoparticle-shape effect. They observed that both velocity and temperature profiles increase for augmenting heat source/sink, thermal radiation, and SWCNT volume fraction with respect to lamina and cylinder shapes.…”
Section: Introductionmentioning
confidence: 99%